Some generalizations of non-unique fixed point theorems of Ćirić-type for (Φ,ψ)-hybrid contractive mappings - Olatinwo, Memudu O. (Annales Mathematicae Silesianae, 2019)
In this article, we establish some non-unique fixed point theorems of Ćirić’s type for (Φ,ψ)-hybrid contractive mappings by using a similar notion to that of the paper [M. Akram, A.A. Zafar and A.A. Siddiqui, A general class of contractions: A-contractions, Novi Sad J. Math. 38 (2008), no. 1, 25–33]. Our results generalize, extend and improve several ones in the literature.